2005
DOI: 10.1128/aem.71.11.7571-7574.2005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Ability of Listeria monocytogenes To Pass through a Membrane Filter by Active Infiltration

Abstract: Listeria monocytogenes infiltrated the reticulate structure of a membrane filter and passed through a filter with pore sizes of 0.45 m and 0.2 m in 6 to 24 h and 5 to 6 days, respectively. Flagellar motility and expansive pressure generated by the growing bacterial population were indicated as the driving forces of infiltration.Listeria monocytogenes is a serious threat to humans because of food-borne infections (2, 11). The organism causes generalized infections by exhibiting a remarkable ability to dissemina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…Scanning electron micrographs (SEM) of uninoculated filters showed broad void spaces with longer distances (Ͼ1.0 µm) between polymer net fibers composing filters (5, 11). Thus, indicated pore-size values with the membrane filters are not morphologically determined ones but are instead functional values for the ordinary pressure filtration method (11). Consistent with these findings, SEM also indicated that the bacteria in the process of infiltration were not remarkably downsizing (5,11).…”
supporting
confidence: 75%
See 4 more Smart Citations
“…Scanning electron micrographs (SEM) of uninoculated filters showed broad void spaces with longer distances (Ͼ1.0 µm) between polymer net fibers composing filters (5, 11). Thus, indicated pore-size values with the membrane filters are not morphologically determined ones but are instead functional values for the ordinary pressure filtration method (11). Consistent with these findings, SEM also indicated that the bacteria in the process of infiltration were not remarkably downsizing (5,11).…”
supporting
confidence: 75%
“…Thus, indicated pore-size values with the membrane filters are not morphologically determined ones but are instead functional values for the ordinary pressure filtration method (11). Consistent with these findings, SEM also indicated that the bacteria in the process of infiltration were not remarkably downsizing (5,11). The semi-quantitative studies showed that required times for the bacterial pass-through were dependent on the indicated filter pore sizes and bacterial species and strains (5).…”
supporting
confidence: 71%
See 3 more Smart Citations